2021
DOI: 10.1051/0004-6361/202039676
|View full text |Cite
|
Sign up to set email alerts
|

Complex organic molecules in protoplanetary disks: X-ray photodesorption from methanol-containing ices

Abstract: Context. Astrophysical observations show complex organic molecules (COMs) in the gas phase of protoplanetary disks. X-rays emitted from the central young stellar object that irradiate interstellar ices in the disk, followed by the ejection of molecules in the gas phase, are a possible route to explain the abundances observed in the cold regions. This process, known as X-ray photodesorption, needs to be quantified for methanol-containing ices. This Paper I focuses on the case of X-ray photodesorption from pure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…More recently, the desorption induced by the irradiation of X-rays, referred to as X-ray photodesorption, was also highlighted as a significant process for ices composed of simple (Dupuy et al, 2018(Dupuy et al, , 2021b and complex molecules (Jiménez-Escobar et al, 2018;Ciaravella et al, 2020;Basalgète et al, 2021a). More importantly, it was suggested that X-ray photodesorption of neutral molecules was strongly dependent on the ice composition via indirect desorption mechanisms (Basalgète et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the desorption induced by the irradiation of X-rays, referred to as X-ray photodesorption, was also highlighted as a significant process for ices composed of simple (Dupuy et al, 2018(Dupuy et al, , 2021b and complex molecules (Jiménez-Escobar et al, 2018;Ciaravella et al, 2020;Basalgète et al, 2021a). More importantly, it was suggested that X-ray photodesorption of neutral molecules was strongly dependent on the ice composition via indirect desorption mechanisms (Basalgète et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…The irradiation experiments allowed us to evaluate the contribution of Auger electrons generated in the ice upon X-Ray absorption. By comparing the yields measured under X-ray irradiation, [8] the dominant role played by XESD and the thermalization of the generated Auger electron is clearly demonstrated. Methanol ices, typically 70 to 100 monolayers (ML) thick, were grown by vapour deposition on a cold substrate (23 K) and irradiated with 505 eV electrons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Comparison of relative desorption yields between ESD (present work) and X-Ray photodesorption. [8] Each data set is normalised to the CH3OH yield. Yields for the black and blue data set shown were calculated using the partial ionisation cross-sections for to CH4 and formic acid (FA), respectively.…”
Section: Electron Induced Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmic-ray induced desorption from CO has also been studied from early on 17,18 and more recently with heavy ions 19 . In several recent papers, we have explored the a Sorbonne Université, Observatoire de Paris, Université PSL, CNRS, LERMA, F-75005, Paris, France; E-mail: dupuy@fhi.mpg.de b Institut de Chimie Physique, UMR 8000, CNRS, Université Paris-Saclay, 91405, Orsay, France c Laboratori Nazionali di Frascati (LNF)-INFN I-00044 Frascati d CERN, CH-1211 Geneva 23, Switzerland astrophysical implications 20 and the details 21 of the X-ray photodesorption process from water ice, as well as X-ray photodesorption from methanol in pure 22 and mixed ices 23 . Other authors also studied X-ray photodesorption from mixed ices 24,25 .…”
Section: Introductionmentioning
confidence: 99%